Perceptions and Applications of AI among High School Students (Docentes 2.0 Journal, 2024)
This study focuses on the technological transformation within the educational sphere, specifically exploring secondary school students' perceptions regarding Artificial Intelligence (AI) in Heredia, Costa Rica. Employing a pragmatic approach and a mixed-methods methodology, data were gathered from 506 students through surveys. A descriptive design was chosen to accommodate the multifaceted nature of the research, with a 'cross-sectional' study type enabling an effective analysis of the phenomenon under investigation. Lastly, the comparative research cut provided detailed and contextual insight into the application of AI in the educational domain. Results revealed diverse opinions on AI in education, with some students already incorporating AI tools in their learning while others were exploring their potential. The significance of ethics in AI applications was emphasized, highlighting the need for education that promotes ethical and conscious use of AI. The study concluded by underscoring the vital role of educators in the transition toward a technologically enriched education and the necessity for students to adapt to new methods of accessing and processing information, such as social networks.
Keywords: Artificial intelligence; ethics; high school education; technological tools